2015
DOI: 10.1007/s10824-015-9248-3
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of fundraising periods and geographic distance on financing music production via crowdfunding in Brazil

Abstract: We conduct an analysis of 1835 pledges to 10 music production projects hosted on the largest Brazilian crowdfunding platform, namely the Catarse Web site, and we assess the relation between the fundraising accumulation period, the donor-entrepreneur distance and the propensity of donors to back projects. Our results suggest a significantly negative association between distance and the value of capital pledged to projects, which is consistent with the notion that the entrepreneur's network of close contacts mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 51 publications
6
33
0
Order By: Relevance
“…In cases of cultural productions facing other cultural barriers because of fragmented and competitive market conditions, as is the case with recorded music, the campaigns are more vulnerable to geography and distance than was demonstrated by a previous study (Agrawal et al, 2015). Our results are more in line with findings related to the effects of distance in other non-English-speaking countries, like the case of Brazil (Mendes-Da-Silva et al, 2016). An explanation might be that those musicians resorting to CCF are predominantly in an early career phase, and use their campaigns to target family, friends and people in their core social network.…”
Section: Discussionsupporting
confidence: 88%
“…In cases of cultural productions facing other cultural barriers because of fragmented and competitive market conditions, as is the case with recorded music, the campaigns are more vulnerable to geography and distance than was demonstrated by a previous study (Agrawal et al, 2015). Our results are more in line with findings related to the effects of distance in other non-English-speaking countries, like the case of Brazil (Mendes-Da-Silva et al, 2016). An explanation might be that those musicians resorting to CCF are predominantly in an early career phase, and use their campaigns to target family, friends and people in their core social network.…”
Section: Discussionsupporting
confidence: 88%
“…The studies confirm some of the factors identified in the more general funding ventures literature. Among these, team characteristics like board members' number, experience, management skills, education, networks (Ahlers et al, 2015), product differentiation (Hu et al, 2015), geographical proximity (Agrawal et al, 2011;2014;Mollick, 2014;Mendes da Silva et al, 2016) and age of the venture (Ahlers et al, 2015) were confirmed as factors that improve the chances of success of crowdfunding campaigns. On the other hand, the funding goal is often associated with a lower probability of success (e.g.…”
Section: Determinants Of Crowdfunding Successmentioning
confidence: 99%
“…Geographical proximity (Agrawal et al, 2011(Agrawal et al, , 2014Mollick, 2014;Mendes da Silva et al, 2016) Cultural similarity (Burtch et al, 2013) "All-Or-Nothing" (Cumming et al, 2014) Project Women (Frydrych et al, 2014) Video pitch (Frydryck et al, 2014) Financial rewards (Ordanini et al, 2011); non-financial rewards (Gerber et al, 2012) Promotional activities (Kuppuswamy & Bayus, 2013) Social media coverage (e.g. Tweets) and features of the platform (Qiu, 2013) Team characteristics, i.e.…”
Section: Crowdfunding and Sustainable Entrepreneurshipmentioning
confidence: 99%
“…According Mendes-Da-Silva, Rossoni, Conte, Gattaz, & Francisco (2015) in Brazil the growth rate is fast, following what happens in Europe, where this type of funding presents itself as an attractive alternative to capital funds and other credit tools. According to information revealed in Statista.com website (see Figure 1) in 2008, the number of CF platforms worldwide increased 38% compared to the previous year.…”
Section: Quick Research On Cf In Brazilmentioning
confidence: 97%